The 2021 WHO classification of tumors of the thymus and mediastinum: what is new in thymic epithelial, germ cell, and mesenchymal tumors?$dstate of the art : concise review - Marx, Alexander; Chan, John K. C.; Chalabreysse, Lara; Dacic, Sanja; Detterbeck, Frank; French, Christopher A.; Hornick, Jason L.; Inagaki, Hiroshi; Jain, Deepali; Lazar, Alexander J.; Marino, Mirella; Marom, Edith M.; et al. (Journal of thoracic oncology, 2022)
This overview of the fifth edition of the WHO classification of thymic epithelial tumors (including thymomas, thymic carcinomas, and thymic neuroendocrine tumors [NETs]), mediastinal germ cell tumors, and mesenchymal neoplasms aims to (1) list established and new tumor entities and subtypes and (2) focus on diagnostic, molecular, and conceptual advances since publication of the fourth edition in 2015. Diagnostic advances are best exemplified by the immunohistochemical characterization of adenocarcinomas and the recognition of genetic translocations in metaplastic thymomas, rare B2 and B3 thymomas, and hyalinizing clear cell carcinomas. Advancements at the molecular and tumor biological levels of utmost oncological relevance are the findings that thymomas and most thymic carcinomas lack currently targetable mutations, have an extraordinarily low tumor mutational burden, but typically have a programmed death-ligand 1high phenotype. Finally, data underpinning a conceptual advance are illustrated for the future classification of thymic NETs that may fit into the classification scheme of extrathoracic NETs. Endowed with updated clinical information and state-of-the-art positron emission tomography and computed tomography images, the fifth edition of the WHO classification of thymic epithelial tumors, germ cell tumors, and mesenchymal neoplasms with its wealth of new diagnostic and molecular insights will be a valuable source for pathologists, radiologists, surgeons, and oncologists alike. Therapeutic perspectives and research challenges will be addressed as well.